PENERAPAN STRATEGI METAKOGNISI PADA PEMBELAJARAN KALOR UNTUK MENGIDENTIFIKASI PROSES BERPIKIR SISWA DALAM MENYELESAIKAN MASALAH - Intan Asriningsi; Duden Saepuzaman; Selly Ferranie (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
This study aimed to identify the students’ thinking process in solving problems while learning the heat material. Applying metacognitive strategies with group investigation methods. Metacognition is defined as an individual's ability to reflect, understand, and control their own thoughts and acts. Therefore, metacognition strategy is a guide to solve problems by considering several alternative solutions. The steps outlined in a journal students' thinking. The students thinking process were observed from of the students' answers in the journal students' thinking. In a the journal students' thinking raised the problem which need to be solved. The students were answering the problem by using basic ability with the results 53.85% of students answered incorrectly as well as the reason, and 46.15% of students answered correctly with specifications of 5.13% were answered with appropriate reasons, and 41.02% were answered with the varied and unsuitable reason. Furthermore, students were given alternative solutions such as Internet browsing and group discussions, so that 82.05% of students change the answers of the problems, especially changing the reasons and 17.95% remained the answer. After that the students were given another alternative solutions in the form of experiments, so the students considered the most appropriate answer from alternatives given. At the end, the students' answers are found 71.79% of students choose an alternative to the answer of the experiment, 17.95% of students responded with answers from the internet, and 10.25% students answer without mentioning the reason. This finding indicates the thinking process of students in solving problems. The use of this strategy makes students think to consider alternative solutions to get a proper solution of the problem. Keywords: Metacognition, Group investigation, heat